Multiplex PCR tests sentinel the appearance of pandemic influenza viruses including H1N1 swine influenza - Mahony, James B. (J Clin Virol, 2009)
BACKGROUND: Since the turn of the century seven new respiratory viruses have infected man and two of these have resulted in worldwide epidemics. Both SARS Coronavirus which quickly spread to 29 countries in February 2003 and H1N1 swine influenza that recently spread from Mexico to 30 countries in three weeks represent major pandemic threats for mankind. Diagnostic assays are required to detect novel influenza strains with pandemic potential. OBJECTIVE: In this report we evaluate the ability of a multiplex PCR test (xTAG™ RVP) to detect new, “non-seasonal” influenza viruses including the H1N1 swine influenza A/swine/California/04/2009. STUDY DESIGN: Laboratory based study using retrospective and prospective specimens. RESULTS: This multiplex PCR test detected the present of non-seasonal (non-H1, non-H3) influenza in 20 of 20 patients infected with H1N1 swine flu virus. In addition to detecting the current swine flu the xTAG™ RVP test detected the H5N1 A/Vietnam/1203/2004 high pathogenicity avian influenza virus that circulated in South East Asia in 2003 as well as 17 out of 17 influenza A viruses representing 11 HA subtypes isolated from birds, swine and horses not yet seen in the human population. CONCLUSION: Based on these results we believe that this molecular test can perform an important role as a sentinel test to detect novel non-seasonal influenza A viruses in patients presenting with influenza-like illness (ILI) and therefore act as an early warning system for the detection of future pandemic influenza threats.